Program Pemetaan Nama Jalan Oleh KKN-T 14 UNIRA Malang di Desa Srigonco Bantur - Alif Achadah; Gilang Saputra; Iqbalul Rizki (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Street names are a vital public information tool that helps people identify locations, find addresses, and reinforce the identity of a region. The availability of street names also supports the effectiveness of administrative services, community mobility, and emergency service access. Srigonco Village, Bantur District, Malang Regency, still faces a lack of street names, making it difficult for residents and visitors to find specific addresses. Based on this situation, students from the 14th Community Service Program (KKN-T) at Raden Rahmat Islamic University (Unira) Malang implemented a community service program involving mapping and installing street names at several strategic locations in the village. The implementation method included field observation, street name data collection, coordination with village officials, design and production, and installation of the street names. This program aims to improve access to location information, clarify regional identity, and support orderly village administration. The results of the activity indicate that the presence of street names provides tangible benefits to the community, particularly in facilitating address searches, improving environmental order, and helping visitors to identify Srigonco Village more easily and effectively.